2020
DOI: 10.1002/glia.23909
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal arrays of particle assembly are essential for normal aquaporin‐4 expression level in the brain

Abstract: Astrocyte endfeet are endowed with aquaporin-4 (AQP4)-based assemblies called orthogonal arrays of particles (OAPs) whose function is still unclear. To investigate the function of OAPs and of AQP4 tetramers, we have generated a novel "OAP-null" mouse model selectively lacking the OAP forming M23-AQP4 isoform. We demonstrated that AQP4 transcript levels were not reduced by using qPCR. Blue native (BN)/SDS-PAGE and Western blot performed on OAP-null brain and primary astrocyte cultures showed the complete deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 64 publications
4
34
0
Order By: Relevance
“…We have already shown that total AQP4 mRNA level is unchanged between WT and M23-null brain (de Bellis et al, 2020). Those data were obtained using qRT-PCR primers specific for the exon-junction II-III and for Exon IV.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…We have already shown that total AQP4 mRNA level is unchanged between WT and M23-null brain (de Bellis et al, 2020). Those data were obtained using qRT-PCR primers specific for the exon-junction II-III and for Exon IV.…”
Section: Discussionmentioning
confidence: 92%
“…The animal model used here was already published (de Bellis et al, 2020 ). OAP‐null mice harboring the M23I point mutation were generated on the C57BL/6J background by Cyagen Biosciences (Santa Clara, CA) using CRISPR/Cas9‐based targeting and homology‐directed repair.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations